Menciptakan Ruang Kreatif melalui Pembuatan Mural Bergaya Dekoratif di SDN 010 Cidadap, Bandung - Darmayanti, Tessa Eka; Chandrahera, Yuma; Santoso, Miky Endro; Levina, Lisa; Effendi, Ismet Zainal (Universitas Nusantara PGRI Kediri, 2024)
SDN 010 Cidadap is a state elementary school in Bandung. This school faces several challenges, such as being listed as the school with the lowest number of student applicants in the city of Bandung. The location of the school is considered to be a trigger, even though it is located on the side of the main road, access is blocked by offices and commercial facilities. This school also lacks artistic values, that can be an attraction to the surroundings and contribute a unique identity of a place. As a result, the school wishes to transform the school atmosphere by presenting an attraction that will encourage the creativity of the school community, particularly students. This hope was realized through Community Service Activities (PKM) in collaboration between the Faculty of Fine Arts and Design, Maranatha Christian University, the Lions Club Bandung social community, and PT Propan Raya to create a creative space through participation in making decorative style murals on school walls. The resulting decorative murals provide freshness to the school environment and can foster pride in the school community. Apart from that, murals can also help students develop their creativity and active participation in school events.